A molecular dynamics-informed probabilistic cross-slip model in discrete dislocation dynamics. (1st January 2021) - Malka-Markovitz, Alon; Devincre, Benoit; Mordehai, Dan
Abstract: We present here a quantitative study of dislocation cross-slip, an essential thermally activated process in deformation of metals, in discrete dislocation dynamics (DDD) simulations. We implemented a stress-dependent line-tension model in DDD simulations, with minimal information from molecular dynamics (MD) simulations. This model allows reproducing in DDD simulations the probabilistic cross-slip rate calculated in MD simulations for Cu in a large range of stresses and temperatures. The implementation of an atomically-scale accurate cross-slip model allows simulating more accurately phenomena such as deformation softening, dislocation-precipitate interaction and dislocation patterning in DDD simulations. Graphical abstract: Image, graphical abstract